The Implications of Forum on China-Africa Cooperation (FOCAC) on Africa’s Regional Integration: Progress or Retrogress? - Obikyere, D,O. (University of Ghana, 2022)
Established in 2000, the Forum on China Africa Relations (FOCAC) has been the major platform driving China’s international relations in Africa. FOCAC is designed to promote commerce, cultural exchanges, development, peace and security, the eradication of poverty, the building of green infrastructure, the improvement of public health, and investment engagements between China and the African Continent. The growing relationship between China and Africa has given rise to the unsettling idea that this collaboration would impede Africa's integration goal. Situated within the analytical tools of supranationalism, the study combines primary data (interviews) with secondary sources: books, book chapters, journal articles, reports and online sources in analysing the implications of FOCAC on Africa’s regional integration drive. The study found that FOCAC makes considerable investment in Africa in the areas of infrastructure and economic cooperation. While there are visible threats because of the Chinese government’s foreign policy of raw material exploitation in Africa and a stronger economic option away from the AU, the study recommends establishment, imposition, and enforcement of monetary and criminal sanctions against Chinese Officials, MNCs, citizens and other actors who do not comply with acceptable standards of operations within the scope of FOCAC and other laws guiding trade and investment within the African continent. Additionally, the Africa Union must take advantage of its admission to FOCAC to demonstrate leadership by charting the African states must follow while negotiating their bilateral accords with China, directed toward achieving the more general, far-reaching objective of a regionally integrated Africa
MA. International Affairs
Keywords: Forum on China Africa Relations (FOCAC); Africa; public health